2006
DOI: 10.1002/ejlt.200600137
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of cholesterol in broth, cream, and butter by probiotic bacteria

Abstract: Assimilation of cholesterol in broth, cream, and butter by probiotic bacteriaHigh serum cholesterol concentrations are associated with the development of coronary heart disease. It has been reported that some cultures of Lactobacillus spp. actively take up cholesterol from laboratory media. In the present study, the abilities of ten probiotic lactic acid bacteria to assimilate cholesterol in broth medium, cream, and butter were tested and compared. The cholesterol reduction ratios of these humanorigin bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 22 publications
1
25
0
1
Order By: Relevance
“…haloplanktis , under these conditions, was about 0.71 µg. It has to be noted that the percentage of cholesterol uptake was in agreement with those previously reported for other bacteria . In addition, the total amount of cholesterol taken up from P .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…haloplanktis , under these conditions, was about 0.71 µg. It has to be noted that the percentage of cholesterol uptake was in agreement with those previously reported for other bacteria . In addition, the total amount of cholesterol taken up from P .…”
Section: Resultssupporting
confidence: 91%
“…It has to be noted that the percentage of cholesterol uptake was in agreement with those previously reported for other bacteria. [17] In addition, the total amount of cholesterol taken up from P. haloplanktis was 0.43 μg/mg total protein. This level is lower than that reported for Escherichia coli grown using an enriched cholesterol medium; [18] in this study, P. haloplanktis was grown without cholesterol supplementation.…”
Section: Resultsmentioning
confidence: 95%
“…Many scientific groups have reported the beneficial effects of probiotics on immunological, digestive and infectious diseases 7, 8. Recently, there has been an explosion of research into the effects of probiotics on lipid metabolism and gut ecology 9–14. We have identified a novel strain Lactobacillus plantarum P‐8 by screening of lactic acid bacteria isolated from traditional dairy products consumed by minority ethnic groups in China.…”
Section: Introductionmentioning
confidence: 99%
“…Even though cholesterol is a major basic block for body tissues, high level of blood cholesterol is one of the causes of hypercholesterolemia and it was shown that 45% of heart attacks in Western Europe and 35% of heart attacks in Central and Eastern Europe are related to this hypercholesterolemia (Aloglu and Öner, 2006;Kumar et al, 2012).…”
Section: Cholesterol-lowering Effectsmentioning
confidence: 99%